2010
DOI: 10.1002/cm.20464
|View full text |Cite
|
Sign up to set email alerts
|

Actin on DNA—An ancient and dynamic relationship

Abstract: In the cytoplasm of eukaryotic cells the coordinated assembly of actin filaments drives essential cell biological processes, such as cell migration. The discovery of prokaryotic actin homologues, as well as the appreciation of the existence of nuclear actin, have expanded the scope by which the actin family is utilized in different cell types. In bacteria, actin has been implicated in DNA movement tasks, while the connection with the RNA polymerase machinery appears to exist in both prokaryotes and eukaryotes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…A second question concerns why JMY combines two very different cellular functions—transcriptional regulation and actin assembly—in one protein. Given the emerging role for nuclear actin in transcription regulation (Skarp and Vartiainen, 2010), it is tempting to speculate that JMY acts as a molecular link between the actin cytoskeleton and the transcription machinery. It will be important to examine transcription- and actin-related functions of JMY in cellular processes, including neuritogenesis, to understand whether they work together or independently.…”
Section: Discussionmentioning
confidence: 99%
“…A second question concerns why JMY combines two very different cellular functions—transcriptional regulation and actin assembly—in one protein. Given the emerging role for nuclear actin in transcription regulation (Skarp and Vartiainen, 2010), it is tempting to speculate that JMY acts as a molecular link between the actin cytoskeleton and the transcription machinery. It will be important to examine transcription- and actin-related functions of JMY in cellular processes, including neuritogenesis, to understand whether they work together or independently.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the nucleocytoplasmic transport of actin tend to be very complex on account of the size of actin and because of the lack of a classical nuclear localization signal (NLS) [14]. It has also been suggested that many actin-binding proteins have NLS, which thus makes it possible to import actin into the nucleus [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, modulation of nuclear actin likely depends and is critically influenced by the signaling context as well as shuttling dynamics of its regulating factors. It is therefore not surprising that the formation of nuclear F-actin has been controversially discussed up to the point that nuclear actin was considered to be entirely or mainly monomeric in its nature (5)(6)(7)(8)(9). Recently, we and others have demonstrated the existence of nuclear F-actin structures in somatic cell nuclei using actin probes, which are specifically targeted to the nucleus (10,11).…”
mentioning
confidence: 99%